A comparative study on the prevalence of caries among grade six students of University of the Philippines Integrated School (UPIS) and Geronimo Santiago Elementary School (GSES) - See, Ana Emilia X.
Dental caries is an infectious microbiological disease of the tooth that results in localized dissolution and destruction of the calcified tissues.(Sturdevant et al 1995). DMFT is the most widely used index in assessing the prevalence of caries. The aim of the study was to compare the prevalence of caries among the grade six students from GSES and UPIS. The study also intended to determine the relationship of the DMFT rates and the following factors: dental programs, monthly family income, OHI-S, dental visits, and diet. A cross-sectional analytical research method was used to study the 88 subjects from the two schools, who were examined orally and have completed the questionnaires. The mean DMFT values of the two schools are GSES=3.863 and UPIS=2.2727. The dental program and OHI-S of the two schools showed a statistically significant result. Only in GSES did diet and income present a significant correlation with mean DMFT rates. Frequency of dental visits exhibited an insignificant relationship with mean DMFT rates. In conclusion, the study demonstrates a significant difference in the mean DMFT values of GSES and UPIS. with the latter having a lower mean that can be attributed to the presence of the dental program in the said school and the OHI-S of the subjects.